Thoracoscopic Surgery for Partial Anomalous Pulmonary Venous Connection with Dual Drainage. Issue 10 (24th August 2015) - Fuchigami, Tai; Gabe, Atsushi; Takahashi, Kazuhiro; Nishioka, Masahiko; Akashige, Toru; Nagata, Nobuhiro
ABSTRACT We report our technique for thoracoscopic surgery for a 15‐year‐old female (body weight, 59 kg) diagnosed with partial anomalous pulmonary venous connection with dual drainage. A large anomalous right lower pulmonary vein (RLPV) was drained into the inferior vena cava and left atrium, along with thoracoscopic ligation and clipping of RLPV and some anomalous hepatic veins. doi: 10.1111/jocs.12606 (J Card Surg 2015;30:764–766)